From the Global to the Local: How International Children’s Rights in Bangladesh Reach the Grassroots Level - Schapper, Andrea (Consilience, 2009)
The Government of Bangladesh has ratified the UN Convention on the Rights of the Child and the ILO Worst Forms of Child Labor Convention. Although national legislation pertaining to children’s rights is inconsistent and the National Child Labor Policy has yet to be adopted, many activities to transport children’s rights principles to underprivileged children have already been initiated in Bangladesh. These mainly take the form of projects by International Organizations or the Bangladesh Government, implemented through local Non-Governmental Organizations or local government structures. Two programs are introduced here, the rural “Food for Education” Program and the urban project, “Prevention and Elimination of Selected Worst Forms of Child Labour in the Informal Economy in Dhaka City”. Both are analyzed in terms of what mechanisms and actor constellations were used to promote children’s rights at the grassroots level. Even though these projects reflect the principles of global norms and transport them to the local people, reaching out to a high number of underprivileged and poor children remains a challenge.